Pre-processing visualization of hyperspectral fluorescent data with Spectrally Encoded Enhanced Representations - Wen Shi (Nature Portfolio, 2020)
Spectral phasor analysis allows unmixing fluorescence microscopy images, but it requires user involvement and has a limited number of labels that can be analyzed and displayed. Here the authors present a semi-automated solution to visualise multiple spectral components of hyperspectral fluorescence images, simultaneously.